A Determination of Brain Damage Induced by Sodium Benzoate Via Changes in Neurotransmitters, Molecular Parameters, Histopathology and Oxidative Damage - Yousef, Mokhtar Ibrahim; AL-Jarrad, Rafal Sattar Jabbar; Kamel, Maher Abd El-naby; El-Shennawy, Lamiaa Khamies (Scientific Journal of Medical Research, 2025)
Objectives: One of the wide uses as food preservative is sodium benzoate (SB) because it has properties such as solubility in water with fungistatic and bacteriostatic and stability. SB has negative effects on long-term even at low doses. Aim of study: our study aimed to determine sub-chronic (90 days) exposure and wide range of different doses (1, 10, 50, 100, 250, 500 and 1000 mg/kg B.W.) of sodium benzoate on brain functions. Results: Sodium benzoate caused changes in the expression of mitochondrial transcription factor A (mtTFA) and peroxisome proliferator activator receptor gamma-coactivator 1? (PGC-1?). In addition, disturbed the cytokine production, deregulated Caspases-3, tumor suppressor protein p53, tumor necrosis factor-? and interliukin-6. Also, the neurotransmitters (norepinephrine, serotonin, dopamine and acetylcholine esterase) were affected, and induced oxidative stress in the brain via increase the levels of free radicals and nitric oxide, and decreased antioxidants enzymes. Conclusion: It was clear from the obtained data that the effect of SB was in a dose dependent manner. This study showed that SB caused neurotoxicity and brain injury after sub chronic exposure especially with the high doses.